227 Impact of feeding Aspergillus subspecies (ssp.) blend and different corn processing methods on finishing beef cattle performance and carcass characteristics - Hopfauf, Stacia M (J Anim Sci, 2020)
The objective of this study was to evaluate the effect of feeding Aspergillus ssp. blend in combination with dry-rolled (DRC) or high-moisture corn (HMC) based finishing diets on performance and carcass characteristics. Crossbred beef steers (n = 320; initial BW = 267 ± 9 kg) were utilized in a generalized randomized block design. Cattle were assigned randomly to pens by initial body weight (BW) and pens were assigned randomly to one of four treatments with 8 pens per treatment for simple effect means. Treatments were set up as a 2 × 2 factorial arrangement with factors consisting of corn processing and 0 g / steer daily or 10 g / steer daily Aspergillus ssp. blend. There were no significant interactions (P ≥ 0.23) observed between corn processing and Aspergillus ssp. blend in the diet; therefore, only main effects are discussed. For the main effect of Aspergillus ssp. blend; no significant differences were observed for dry-matter intake (DMI), average daily gain (ADG), feed efficiency (G:F), hot carcass weight (HCW), or carcass traits (P ≥ 0.78). Cattle fed Aspergillus ssp. blend had a greater 12(th) rib fat (P = 0.05). For the main effect of corn processing, cattle fed DRC had heavier HCW and final BW (P = 0.04), greater ADG (P = 0.05), and greater DMI (P < 0.01). However, steers fed HMC had greater G:F (P < 0.01) compared to DRC. These data suggest that feeding Aspergillus ssp. blend in either with dry-rolled or high moisture corn diets did not significantly improve performance or carcass characteristics in finishing beef steers. While feeding HMC improved feed efficiency compared to DRC, feeding DRC increased ADG (and also DMI) compared to HMC.